Counterfeiting credit cards. Displacement effects, suitable offenders and crime wave patterns - Mativat, François (The British journal of criminology, 1997)
A displacement-induced crime wave model assumes that changes in crime opportunities will motivate a significant subset of offenders to engage in similar crime switching adaptations, expectation being that the crime wave will therefore be associated with a concomitant decrease in other related offences. This paper locates a particular crime wave (a 1992-94 wave in counterfeit credit card frauds), identifies a set of related offences (stolen-based credit card frauds) and argues that the expected displacement effect triggered by the marketing of compact and efficient encoding and embossing equipment (as well as sophisticated photocopying and printing devices) did not materialize, in practice, at least in the setting we have analysed (Montreal). Even though stolen-based and altered credit card frauds were tightly related offences and involved a homogeneous population of offenders, the actual difference in pay-off was not significant enough to trigger systematic switching in crime tactic preferences; moreover, offenders willing to participate in sophisticated pure' counterfeit credit card frauds could not, as a matter of fact, take advantage of such an option even if they wished to do so (mainly because they did not have the right (ethnic) connections)